SISTEM AKUNTANSI PEMBELIAN KREDIT PADA PT. GLOBAL MULTIPARTS - Fera Lufhidarani Pranita; Wulandari Suhanda (JURNAL LENTERA AKUNTANSI, 2024)
In general, in a company, having purchase transactions is useful for procuring merchandise. Having goods available for sale will generate profits for the company. This research aims to find out: What is the accounting system for credit purchases at  PT.  Global  Multiparts,  how is  the  internal  control  in  the  credit  purchase accounting system at PT. Global Multiparts, what is the internal control system at PT. Global Multiparts has been running well and correctly, what are the healthy practices at PT. Global Multiparts To obtain data and information in preparing research on the accounting review of credit purchases of merchandise required in this research, the author conducted research on research and theoretical foundations as a guide so that the research focus is in accordance with the facts in the field. The research results show that the implementation of Credit Purchase Systems and Procedures at PT. Global Multiparts is running well, but there are still shortcomings such as related functions that are still not separated.